Desmoplastic small round cell tumor cancer stem cell-like cells resist chemotherapy but remain dependent on the EWSR1-WT1 oncoprotein - Magrath, Justin W.; Kang, Hong-Jun; Hartono, Alifiani; Espinosa-Cotton, Madelyn; Somwar, Romel; Ladanyi, Marc; Cheung, Nai-Kong V.; Lee, Sean B. (Frontiers in Cell and Developmental Biology, 2022)
Desmoplastic Small Round Cell Tumor (DSRCT) is a rare and aggressive pediatric cancer driven by the EWSR1-WT1 fusion oncogene. Combinations of chemotherapy, radiation and surgery are not curative, and the 5-years survival rate is less than 25%. One potential explanation for refractoriness is the existence of a cancer stem cell (CSC) subpopulation able escape current treatment modalities. However, no study to-date has examined the role of CSCs in DSRCT or established in vitro culture conditions to model this subpopulation. In this study, we investigated the role of stemness markers in DSRCT survival and metastasis, finding that elevated levels of SOX2 and NANOG are associated with worse survival in sarcoma patients and are elevated in metastatic DSRCT tumors. We further develop the first in vitro DSRCT CSC model which forms tumorspheres, expresses increased levels of stemness markers (SOX2, NANOG, KLF4, and OCT4), and resists doxorubicin chemotherapy treatment. This model is an important addition to the DSRCT tool kit and will enable investigation of this critical DSRCT subpopulation. Despite lower sensitivity to chemotherapy, the DSRCT CSC model remained sensitive to knockdown of the EWSR1-WT1 fusion protein, suggesting that future therapies directed against this oncogenic driver have the potential to treat both DSRCT bulk tumor and CSCs.